PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU DAN KARYAWAN PADA SMK KESEHATAN GREEN PUTRA MEDIKA MADIUN - Rosyidi, Mohammad (Jurnal Likhitaprajna, 2019)
Improving the achievement of teachers and employees in an educational institution requiressoftware and hardware. Software requirements include the Principal's leadership style,regulations, and School environment. While hardware is a physical facility andinfrastructure. Both of these needs must be balanced and in accordance with the missionand vision that has been declared so that there is no imbalance in improving employeework performance. The purposes of this study was to find out (1) knowing leadership atHealth Vocational School Green Putra Medika of Madiun, (2) work environment at HealthVocational School Green Putra Medika of Madiun, (3) Teacher and EmployeePerformance at Health Vocational School Green Putra Medika of Madiun, (4) the influenceof leadership and work environment on the performance of Teachers and Employees at atHealth Vocational School Green Putra Medika of Madiun. This type of research isexperimental research. The subjects of the study were the principal and teachers andemployees of Health Vocational School Green Putra Medika of Madiun. The results showedthat there was not an influence of leadership and school environment on the performance ofteachers and employees. It can be proven that the value of F count is 2194. After convertingwith F table based on the numerator dk = k and the denominator dk = (n-k-1) with an errorlevel of 5%, it can be seen in the table of values for the distribution of F (attachment) thevalue of 4.95. It turns out that Fcount is greater than Ftable. Thus it can be stated that theinfluence of leadership, work environment, and organizational support together onpersonal performance is not significant. Keywords: leadership, work environment, performance